2022
DOI: 10.1155/2022/8682316
|View full text |Cite
|
Sign up to set email alerts
|

Hydroalcoholic Extract of Sechium edule Fruits Attenuates QT Prolongation in High Fat Diet-Induced Hyperlipidemic Mice

Abstract: The present study aimed to evaluate the effect of hydroalcoholic extract of Sechium edule (S.E.) fruits on lipid profile and electrocardiogram (ECG) parameters in high fat-diet (HFD) induced hyperlipidemic mice. In this study, grouping of animals was done as described below (n = 6), where group 1 is normal control, group 2 is HFD control, group 3 is HFD + atorvastatin (10 mg/kg), group 4 is HFD + S.E. extract (200 mg/kg), and group 5 is HFD + S.E. extract (400 mg/kg). The first 3 weeks animals were supplemente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…With the gradual deepening of biotechnology research, some molecular compounds have been found to have impacts on some diseases. For example, F. S. Mohammed et al 12 showed that sechium edule extract results in the prolongation of QT or QTc and RR intervals and increases the heart rate in high-fat diet-challenged mice. S. Taifa et al 13 found that copper nanoparticles have an excellent effect on mastitis.…”
Section: Discussionmentioning
confidence: 99%
“…With the gradual deepening of biotechnology research, some molecular compounds have been found to have impacts on some diseases. For example, F. S. Mohammed et al 12 showed that sechium edule extract results in the prolongation of QT or QTc and RR intervals and increases the heart rate in high-fat diet-challenged mice. S. Taifa et al 13 found that copper nanoparticles have an excellent effect on mastitis.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment mainly focuses on invigorating Qi and nourishing Yin, moistening the intestines, and relieving constipation [6]. Various academic publications have reported on the Chinese herbal extracts'efects in treating intractable diseases [7][8][9], and the efects in treating constipation have also been confrmed [10].…”
Section: Introductionmentioning
confidence: 99%
“…In the case of hyperlipidemia treatment, numerous medicinal plants have been used traditionally. Among them, Curcuma xanthorrhiza (Yasni et al, 1993), Sechium edule (Mohammed et al, 2022), and Syzigium polyanthum (Hartanti et al, 2019) have been reported to reduce serum lipid levels. In a previous study, extract combination of Sechium edule fruit, Syzigium polyanthum leaf, and Curcuma xanthorrhiza rhizome showed a good effect in reducing cholesterol total and triglyceride levels on male rats induced by high cholesterol diet (Agustini et al, 2006).…”
Section: Introductionmentioning
confidence: 99%